RELIGIOSITY AMONG BOSNIAN YOUTH – ATTITUDES TOWARDS ISLAM AND PRACTICAL WORSHIPPING OF IT - Delić, Haris (Scriptura Indonesia, 2023)
Interest in individuals’ religious beliefs has a long tradition in philosophy, sociology and psychology and attempts are made to understand the spiritual and physical in humans. This quantitative study investigates the religiosity of young people, primary and secondary school students, in Bosnia and Herzegovina (henceforth BH) and their practical manifestation of religious activities. The results indicate that the Bosnian primary and high school students are not largely religious and their religiosity is not largely expressed in their practical performance of religious duties, such as praying, reading a Holy book and visiting a mosque. Moreover, the research points out that young people in BH are quite religious when it comes to external exposure to religion and a little less when it comes to the practical implementation of religious regulations that are mandatory in Islam. Friday prayer for men is a religious obligation that is taken more seriously and performed than other daily prayers that are also obligatory. This research contributes to a clearer insight into the practical religiosity of young people in BiH and helps in understanding the priorities for improving and increasing the religiosity of young people. Also, this work can serve as a basis for other more comprehensive research in this field.